2021
DOI: 10.1007/s43621-021-00039-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prioritization of risk factors in the management of Halal supply chain management

Abstract: In the competitive globalized market, risk management is an important aspect of the supply chain, but it becomes crucial to the management of a faith-based supply chain. The halal supply chain is an emerging research era at an early stage. To retain the halalness from procurement to end customer, this research was aimed to identify and prioritize the important risk elements for managing the HSC. For this purpose, a literature review was studied, 42 risk factors, classified into seven dimensions, were categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In developing countries, outsourcing practices are not well established, and in the case of halal, it becomes more challenging to choose the right partner for outsourcing. Sarwar et al (2021) claim that outsourcing practices are one of the major challenges of halal logistics. Therefore, it is recommended that halal-producing firms should rely on credible halal certification and try to store their product in a halal warehouse or be transported through halal-certified transportation.…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, outsourcing practices are not well established, and in the case of halal, it becomes more challenging to choose the right partner for outsourcing. Sarwar et al (2021) claim that outsourcing practices are one of the major challenges of halal logistics. Therefore, it is recommended that halal-producing firms should rely on credible halal certification and try to store their product in a halal warehouse or be transported through halal-certified transportation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by Khan et al (2021b) and Kumar et al (2021) claimed that MCDM techniques such as analytical hierarchy process, technique for order of preference by similarity to ideal solution (TOPSIS) and BWM are superior for evaluating risk elements and risk dimensions of the halal food supply chain. Moreover, Sarwar et al (2021) found that the risk of halal food supply chain problems can be solved by MCDM approaches. They examined automatic process risks using Elimination Et Choix Traduisant La Realite II and failure modes and effects analysis (FMEA) to identify and eliminate possible failures and evaluate the risks from design, system and process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In prioritizing halal risk factors in HSC management, a study by Sarwar et al (2021) found that 42 risk factors were identified in seven dimensions from experts’ opinions. The categorization of risk spans seven dimensions, encompassing market, sustainability, sourcing, logistics and production, information technology, as well as outsourcing and planning-related risks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study emphasizes the importance of risk management in faith-based supply chains, particularly the halal supply chain [8]. The study identifies and prioritizes risk elements for managing the Halal Supply Chain (HSC) using a fuzzy best-worst method.…”
Section: Introductionmentioning
confidence: 99%